(untitled) (Research, Society and Development, 2020)
Objective: To describe and analyze incidents not specified in the national health examination notification program (NOTIVISA) in Brazil from 2014 to 2019. Methodology: It is a quantitative, descriptive, retrospective study; the epidemiological profile of the notifications registered in NOTIVISA was analyzed. Results: The incidents were recorded by macro-regions, where 44.1% confer to the Southeast region; the states of Minas Gerais (21.20%), São Paulo (16.08%) and Paraná (12.22%) had the highest number of notifications in the period; 93.44% of the incidents occur in hospitals, among which 52% occur in the hospitalization sectors. As for types, 25% were classified as failures during health care, pressure ulcers (18.38%) and 30% as "Others"; 52% of the incidents were classified as mild and 31% were not classified as to severity; as for sex, there was no significant difference; in the age group of reported incidents, they mainly occur among adults (33.26%) and the elderly (38.90%). Conclusion: The notification system is an essential tool for monitoring, control and quality of health services, an end to the investigation of adverse events and promotes improvements in health service, patient safety, cost reduction.